PGAM5 deacetylation mediated by SIRT2 facilitates lipid metabolism and liver cancer proliferation - Fu Gongyu; Li Shi-Ting; Jiang Zetan; Mao Qiankun; Xiong Nanchi; Li Xiang; Hao Yijie; Zhang Huafeng (Acta Biochimica et Biophysica Sinica, 2023)
Tumor metabolic reprogramming and epigenetic modification work together to promote tumorigenesis and development. Protein lysine acetylation, which affects a variety of biological functions of proteins, plays an important role under physiological and pathological conditions. Here, through immunoprecipitation and mass spectrum data, we show that phosphoglycerate mutase 5 (PGAM5) deacetylation enhances malic enzyme 1 (ME1) metabolic enzyme activity to promote lipid synthesis and proliferation of liver cancer cells. Mechanistically, we demonstrate that the deacetylase SIRT2 mediates PGAM5 deacetylation to activate ME1 activity, leading to ME1 dephosphorylation, subsequent lipid accumulation and the proliferation of liver cancer cells. Taken together, our study establishes an important role for the SIRT2-PGAM5-ME1 axis in the proliferation of liver cancer cells, suggesting a potential innovative cancer therapy.